Rancang Bangun Timbangan Otomatis Granula Obat Yang Dilengkapi Chamber Berbasis Arduino Uno - Hasmah Hasmah; Risnawaty Alyah; Usman Umar; Sitti Fatimang; LD Muh Dandi (Lontara Journal of Health Science and Technology, 2023)
The terms granule and granulation are familiar terms in the pharmaceutical field. Granulation activities cannot be separated from the weighing process. Granules are lumps of smaller particles with an uneven shape that become like a single larger particle. In general, pharmacists still use analytical balances to weigh. Weighing using an analytical balance tends to be inefficient because it takes a long time. In this study, a weighing system was designed with the function of automatically weighing drug granules and equipped with a container to accommodate the granules so that there is no need to manually load the granules onto the scales. The purpose of designing this tool is to make it easier for pharmacists to weigh drugs during granulation and make drug preparations. The design of this tool uses a load cell sensor, a servo motor to open and close the flow rate of drug granules from the container automatically, and a DC motor to help accelerate the flow rate of drug granules to the container, which is detected by the load cell sensor. Implementation of the results of this study can be used by laboratory personnel to weigh chemical substances in the form of powders and pharmacists to make it easier to weigh medicine granules. The results of the readings from the automatic weighing device are compared with the results from digital scales, which show an average deviation of 40%.